Correlates of the Timely Initiation of Complementary Feeding among Children Aged 6-23 Months in Rupandehi District, Nepal - Dilaram Acharya; Radha Subedi; Kwan Lee; Seok-Ju Yoo; Salila Gautam; Jitendra Kumar Singh (MDPI AG, 2018)
Although the predictors of the timely initiation of complementary feeding are well-known elsewhere, there is less awareness of the topic in Nepal. The current study was undertaken to identify the correlates of timely initiation of complementary feeding among children aged 6–23 months. A community-based cross-sectional study was conducted in the Rupandehi district, Nepal. A total of 155 mother-child pairs were selected using a simple random sampling technique. Logistic regression with adjustment for potential confounders was employed to examine the independent association between risk factors and the timely initiation of complementary feeding. Fewer than 3 in 5 children aged 6–23 months received complementary feeding at the recommended time. Literate mothers and a maternal occupation in the service or business sectors were found to be associated with complementary feeding at 6 months. In addition, child characteristics such as birth order, male children, and those fed micronutrients were also more likely to have been received complementary feeding at 6 months than their counterparts. Maternal education and occupation, and child characteristics such as, birth order, male gender, and micronutrient consumption, which are correlates of the timely initiation of complementary feeding, suggest that the Nepalese Infant and Young Child Feeding (IYCF) programme should target these predictors while designing preventive strategies.